The Influence of Attitudes, Subjective Norms and Behavioral Control on Purchasing Decisions: A Case Study at Otewe Kopi Surabaya - Pramudya, David Ndaru Aji; Setyadi, Taufik; Syah, Mirza Andrian (UNIVED Press, 2026)
The development of coffee consumption in Indonesia has shown a significant increase over the past decade, particularly among urban communities and younger generations. Coffee is no longer merely perceived as a beverage but has become part of a lifestyle associated with social activities and productivity. This trend has fueled the rapid growth of the coffee shop industry, including Otewe Kopi Surabaya, which targets the young consumer segment. This study aims to analyze the influence of attitude, subjective norms, and perceived behavioral control on consumer purchase decisions at Otewe Kopi Surabaya. Employing the Theory of Planned Behavior (TPB) framework, this research adopts a quantitative approach through a survey method. Data were collected using questionnaires distributed to 96 respondents who were customers of Otewe Kopi. The results indicate that all constructs meet the criteria for convergent validity, discriminant validity, and reliability. The R² value of 0.677 reveals that 67.7% of the variance in purchase decisions can be explained by attitude, subjective norms, and perceived behavioral control. The study concludes that these three core variables of the TPB have a significant and positive influence on consumer purchase decisions. Theoretically, this study strengthens consumer behavior models from psychological and social perspectives, while practically providing insights for business practitioners to develop effective marketing strategies by fostering positive attitudes toward the brand, reinforcing supportive social norms, and enhancing perceptions of ease in purchase.